Enhanced removal of Cr(VI) from aqueous solution by stabilized nanoscale zero valent iron and copper bimetal intercalated montmorillonite - Wang, Yin; Gong, Yishu; Lin, Naipeng; Yu, Lan; Du, Baobao; Zhang, Xiaodong (Journal of colloid and interface science, 2022)
[Display omitted] Batch experiments were conducted to study the Cr(VI) removal by nanoscale zero valent iron and copper intercalated montmorillonite (MMT-nFe0/Cu0) nanocomposite. MMT-nFe0/Cu0 was characterized using SEM, TEM, XRD, FTIR, N2 adsorption–desorption isotherms and XPS. The results demonstrated that highly dispersed nanoscale Fe0/Cu0 (nFe0/Cu0) were successfully introduced into the montmorillonite (MMT) layers. In the reaction process, the combination of Cu0 and Fe0 acted as a galvanic cell, and electrocorrosion not only speeded up the reaction rate, but also increased reduction activity of nFe0. MMT-nFe0/Cu0 as an excellent carrier had good functions in dispersing nFe0 and Cu0 particles, pH buffering and could keep nFe0 and Cu0 particles from being released. Besides, no iron ions and very low concentrations of copper ions released in the reaction system, which greatly avoided the influence of secondary environmental pollution.